Fateful Fragments New Papyrological Evidence of the Lot Oracle Sortes Astrampsychi and Related Sources from Egypt and Elsewhere - Naether, Franziska 1980- (2025)
After the publication of my monograph on the Sortes Astrampsychi (F. Naether, Die Sortes Astrampsychi: Problemlösungsstrategien durch Orakel im römischen Ägypten, Orientalische Religionen in der Antike 3 [Tübingen: Mohr Siebeck, 2010]), interest in ancient lot oracles and their traditions has continued to grow. This paper aims to achieve two main objectives: first, to introduce the Sortes Astrampsychi and present new papyrological evidence from two papyrus fragments currently being prepared for inclusion in the volume P. Lips. 3. These fragments, housed in the Papyrus Collection of Leipzig University, Germany, provide insights into the manuscript tradition and the societal context surrounding this ritual text. Second, over the past decade, additional sources on lot oracles and divinatory practices employing sortition and hemerologies have emerged. These texts, written in Egyptian (Demotic and Hieratic), Latin, and Arabic, form a crucial corpus for understanding the techniques, religious practices, and social dynamics of the sortes genre, including information about sortition devices such as six-sided dice and knucklebones (astragaloi).
Keywords: Greco-Roman Egypt; Comparative Religion; dice; Divination; hemerology; lot oracles; pyrology; sortes